Follicular dynamic and repeatability of follicular wave development in Peranakan Ongole (PO) cattle - Muhammad Imron; Iman Supriatna; . Amrozi; Mohamad Agus Setiadi (Indonesian Center for Animal Research and Development (ICARD), 2016)
Superovulation treatment on PO cattle (Bos indicus) was less responsive compared to Bos taurus breed. It might due to the difference of their follicular dynamic. This study was conducted to investigate the follicular dynamics and its repeatability in PO cattle. Follicular dynamics observations conducted on 9 cows trough ultrasound scanning every day. Observations of wave patterns repeatability were performed in 6 cows which its wave pattern already known on the next consecutive IOI. Research result indicated that PO cattle had 3 (66%) and 4-waves (34%) pattern. The first wave of 3 and 4-waves pattern emerged on day -0.4+0.9 and 1.4+1.1 respectively. The second wave of 3 and 4-wave pattern emerged on day 9.8+1.5 and 7.4+1.9 respectively. The pattern of 3 waves has a longer follicle dominant duration (11.6+1.5 day) in the first wave of estrous cycle, compared with 4 waves pattern (10+2.92 and 7+1.00 day respectively). The growth rate of dominant follicle was not different significantly between the 3 and 4-waves pattern (0.87+0.23 and 0.94+0.25 mm/day respectively). Similarly, ovulatory follicle diameter between 3 and 4-waves pattern was also not different significantly (12.24+12.34 and 12.30+12.23 mm respectively). Observation of wave patterns repeatability in 6 PO cows indicated that PO cattle had high repeatability in follicular wave pattern (0.88) and the number of growing follicle was 0.91. This study resulted data for dynamic of follicular development, wave pattern, its repeatability which be expected to design the protocol of superovulation treatment or other reproduction technologies based on follicular dynamic to improve its result in PO cattle.